If $f:\mathbb N\to\mathbb Z$ satisfies:

$$\forall n,m\in\mathbb N\,, n+m\mid f(n)+f(m)$$

How to show that this implies:

$$\forall n,m\in\mathbb N,\,n-m\mid f(n)-f(m)?$$

I was almost incidentally able to prove this by classifying such functions, but that seems circuitous for such a result. Is there a proof that is (more) direct?


This is actually pretty easy. Let $n>m$, and take an $N$ such that $N(n-m)>m$. Set $a=N(n-m)-m$. Then $$ m+a=N(n-m),\qquad n+a=m+a+n-m=(N+1)(n-m). $$ Now $$ f(n)-f(m)=f(n)+f(a)-(f(m)+f(a)), $$ but by assumption $n-m\mid f(m)+f(a)$ and $n-m\mid f(n)+f(a)$, and we are done.

  • $\begingroup$ Yeah, that was exactly what I was looking for, thanks! $\endgroup$ – Thomas Andrews Jun 4 '14 at 19:42
  • $\begingroup$ You are welcome. $\endgroup$ – Vladimir Jun 4 '14 at 19:43
  • 4
    $\begingroup$ i.e. $\ \ \ \begin{eqnarray} && n\!-\!m\!\!\!&&\mid \ n\!+\!a\!\!\!&&\mid \ \color{#0a0}{f_{\large n}\!+f_{\large a}}\\ \Rightarrow &&n\!-\!m\!\!\!&&\mid m\!+\!a\!\!\!&&\mid \color{#c00}{f_{\large m}\!+f_{\large a}}\end{eqnarray}\Bigg\}\,\Rightarrow\ n\!-\!m\mid (\color{#0a0}{f_{\large n}\!+f_{\large a}})-(\color{#c00}{f_{\large m}\!+f_{\large a}}) = f_{\large n}\!-f_{\large m}\ $ $\endgroup$ – Bill Dubuque Jun 4 '14 at 22:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.